Nanographene oxide modified fiber reinforced cementitious composites: Thermomechanical behaviour, environmental analysis and microstructural characterization - Yildirim, Pinar; Erdem, Savas; Uysal, Mucteba (ELSEVIER SCI LTD, 2024)
A novel fiber reinforced cementitious composites was developed by incorporating microencapsulated phase change materials (PCMs) and nanographene oxide (NGO) to enhance the composites' thermal properties without compromising the compressive strength. Regarding the thermo-mechanical properties, with the addition of NGO, while mechanical properties improve, thermal mass increases and the heat storage ability of the produced composite material enhances. In this situation; it can be interpreted that it will be possible to benefit more from the energy stored by PCMs, as the energy required to change the temperature of the unit mass of the material will decrease. The environmental impact assessment has also revealed that CO2 emissions from production increase with the use of PCMs. However, it has been determined that the addition of NGOs will make a positive contribution to the life cycle, as CO2 emissions resulting from cement will decrease. In conclusion, a novel fiber reinforced composite with enhanced thermal and mechanical properties by combining PCMs and NGO has shown a great potential for environmentally friendly buildings with the integration of structure, energy conservation and long term durability.
Keywords: Nanographene oxide; Cementitious composites; Extreme environment; Thermal behaviour; Fractal analysis; PHASE-CHANGE MATERIALS; LIFE-CYCLE; CONCRETE; PERFORMANCE; DESIGN; ENERGY; IMPACT; Materials Science